2015
DOI: 10.1098/rstb.2014.0042
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion and urothelial bladder cancer: the role of cadherin switching and related phenomena

Abstract: Cadherins are mediators of cell-cell adhesion in epithelial tissues. E-cadherin is a known tumour suppressor and plays a central role in suppressing the invasive phenotype of cancer cells. However, the abnormal expression of N-and P-cadherin ('cadherin switching', CS) has been shown to promote a more invasive and m alignant phenotype of cancer, with P-cadherin possibly acting as a key mediator of invasion and metastasis in bladder cancer. Cadherins are also implicated in numerous signalling events related to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 135 publications
(298 reference statements)
2
40
0
6
Order By: Relevance
“…It is supposed that these dysregulated lncRNAs in different grade bladder cancer and normal urothelium may participate in biological processes of cancer [25][26][27][28]. Bryan RT1 et al found that N-and P-cadherin related to the cadherin cell adhesion and was the potential targets for the inhibition of cancer progression in bladder cancer [29]. Tomasetti et al proved DNA replication errors mutations were responsible for two-thirds of the mutations in human cancers by analyzing cancer genome sequencing and epidemiological data [30].…”
Section: Discussionmentioning
confidence: 99%
“…It is supposed that these dysregulated lncRNAs in different grade bladder cancer and normal urothelium may participate in biological processes of cancer [25][26][27][28]. Bryan RT1 et al found that N-and P-cadherin related to the cadherin cell adhesion and was the potential targets for the inhibition of cancer progression in bladder cancer [29]. Tomasetti et al proved DNA replication errors mutations were responsible for two-thirds of the mutations in human cancers by analyzing cancer genome sequencing and epidemiological data [30].…”
Section: Discussionmentioning
confidence: 99%
“…In an environment of degradation and destabilization of cell-cell adhesion and decreased E-cadherin expression, β-catenin is released into the cytoplasm causing it to accumulate and eventually lead to nuclear translocation (25). Cadherin switching is a hallmark of EMT, where E-cadherin can be replaced by an abnormal expression of N-cadherin without changes in E-cadherin levels (26). This event may be affected by cytokines and growth factors (27).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, activation of WNT signaling cascade by tumor cells owing to decreased E-cadherin levels, loss of β-catenin expression, its nuclear translocation and increased transcriptional activity have been examined to be associated with epithelial plasticity of tumor cells, disease aggression and metastasis formation. One of the serious implications of cadherin switching include the development of cancer stem cell phenotype and this makes the cadherin cell adhesion molecules and associated pathways, the probable target candidates for inhibition of cancer progression [16] . Tumor stroma/microenvironment has been shown to regulate tumor behavior by maintaining UroCSC population, its properties and EMT.…”
Section: Urothelial Cancer Stem Cells and Epithelial Plasticitymentioning
confidence: 99%